(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2017)
نفذ هذا العمل لدراسة إمكانية تحويل الفوسفور من الشكل المعدني إلى الشكل العضوي ضمن تركيب السماد العضوي الصناعي (الكومبوست) بقصد زيادة قيمته التسميدية من خلال إضافة مستويات مختلفة من العناصر الأساسية الصغرى للمادة الخام للكومبوست المكونة من (نشارة مخلفات تقليم أشجار الأكاليبتوس) خلال فترة تخمرها وتحولها إلى كومبوست. تم تصميم التجربة على أساس إضافة العناصر السمادية المعدنية الكبرى والصغرى (Mineral Fertilizers) لنشارة مخلفات تقليم أشجار الأكاليبتوس كمادة أم للكومبوست الصناعي. حيث كان تركيز العناصر الكبرى فيها ثابتاً، أما العناصر الصغرى (Trace Elements, TE) المكونة من خليط متوازن أساسه أملاح هوغلاند (Hoagland)، من (Fe, Mn, Zn, Cu, B, Mo)، فقد أضيفت بأشكال معدنية ((Mineral Forms، بثلاث مستويات من هذه الخلطة السمادية (TE0,TE1,TE2) (0, 55.84, 111.68 mg)، لكل (1) كغ من المادة الجافة وأربع مكررات. وبعد التخمير لمدة (123 يوم)، تم تقدير الفوسفور المرتبط والذائب في مادة الكومبوست المنتج لكل من المعاملات الثلاث كما تم تقدير الكربون العضوي وحساب النسبة Pفي الكومبوست الناتج في نهاية فترة التخمير. أظهرت القياسات والتحاليل أنه مع زيادة تراكيز العناصر النادرة المضافة إلى وسط التخمير، هناك زيادة ملحوظة في نسبة الفوسفور المرتبط وانخفاضا في النسبة Pفي الكومبوست الناتج مقارنة مع مستوياتها في المادة الخام للكومبوست. This work is carried out to study the average of phosphorus sequestration into the structure of the composted matter, in order to increase its fertilization value through addition of different levels of trace elements to the eucalyptus Sawdust as a raw material for composting during the fermentation processes. The experiment was designed on the basis of adding macro and micro essential elements as mineral fertilizers to eucalyptus Sawdust as a parent material for compost. Where the concentrations of macro elements were kept constant, but the trace elements which consisted of a balanced mixture of (Mo, B, Cu, Zn, Mn, Fe) based on Hoagland nutrient salts, were added in the mineral forms through three levels (0, 55.84 and 111.68 mg), (TE0,TE1,TE2), for each kg of dry matter, and four replications. After fermentation for a 123 days, the soluble, bound phosphorus and the organic carbon in the produced compost for all treatments, were estimated and the C/P ratios were calculated. The results showed that, there is a positive relationship between the average of phosphorus sequestration and increasing the concentration of trace elements in the composting materials during fermentation process, while C/P ratio correlated negatively with the progress of the fermentation processes in comparison with their values in the raw material of the compost.